Seasonal influence on hematologic values and hemoglobin electrophoresis in Brazilian Boa constrictor amarali - Machado, Carla C.; Silva, Luis F. N.; Ramos, Paulo R. R.; Takahira, Regina Kiomi [UNESP] (Amer Assoc Zoo Veterinarians, 2006)
As ectothermic animals, snakes depend exclusively on the environment for proper temperature maintenance, which may greatly influence their activity. Twenty-five adult Boa constrictor amarali snakes maintained in captivity were used to determine the influence of seasons on their hematologic values and electrophoretic profile of hemoglobin. A complete blood cell count (CBC) and examination for hemoparasites were performed in the summer and winter of 2004. Hemoglobin was stored for later electrophoresis. Significant differences (P < 0.05) were obtained in RBC, WBC. lymphocyte, thrombocyte, and monocyte counts, demonstrating the importance of the period of the year in the interpretation of reference values in these animals. Two snakes were detected with blood parasites (Hepatozoon sp.) in the winter and four in the summer. although it appears that their presence did not cause any significant alterations in the CBC. The electrophoretic analysis of the samples demonstrated two-four hemoglobin bands in this species.
Keywords: Boa constrictor; electrophoresis; hematology; hemoglobin; hemoparasites; season